Up-conversion quantum yields of SrF2:Yb3+, Er3+ sub-micron particles prepared by precipitation from aqueous solution. Issue 3 (4th January 2018) - Kuznetsov, S.; Ermakova, Yu.; Voronov, V.; Fedorov, P.; Busko, D.; Howard, I. A.; Richards, B. S.; Turshatov, A.
Abstract : Herein, we report near-infrared-to-visible up-conversion (UC) in SrF2 :Yb 3+, Er 3+ sub-micron crystals prepared via a facile route in an aqueous solution. Abstract : Herein, we report near-infrared-to-visible up-conversion (UC) in SrF2 :Yb 3+, Er 3+ sub-micron crystals prepared via a facile route in an aqueous solution. Subsequent calcination at 600 °C allows us to achieve good UC quantum yields, reaching 2.8% at an excitation power density of 10 W cm −2 for a sample doped with 2 mol% of Yb 3+ and 2 mol% of Er 3+ . This UC quantum yield of SrF2 :Yb 3+, Er 3+ is in the range of record UC quantum yields reported in the literature for standard host systems such as La2 O2 S, BaY2 ZnO5 and NaYF4 phosphors. Interestingly, the 2 mol% of Yb 3+ required to achieve optimal UC in the SrF2 host is much lower than the amount of Yb 3+ required in the other host systems. Furthermore, we studied the population and depopulation kinetics of the Er 3+ : 2 H9/2, Er 3+ : 2 H11/2, 4 S3/2 and Er 3+ : 4 F9/2 states using time-resolved photoluminescence measurements in order to provide insight into the UC mechanism. The facile preparation method combined with high UC quantum yield makes SrF2 :Yb 3+, Er 3+ materials attractive candidates for solar energy harvesting, sensors, solid state lasers, and luminescent markers.